DAMPAK KINERJA KEPALA SEKOLAH DALAM MENINGKATKAN MUTU TENAGA PENDIDIK DI SMAIT AL MULTAZAM 2 LINGGAJATI KUNINGAN - Ariyanto; M Syahru Assabana; Suklani; Moh Ahsan (JISPENDIORA Jurnal Ilmu Sosial Pendidikan Dan Humaniora, 2023)
This study aims to determine the performance of school principals in improving the quality of teaching staff, influencing factors and efforts made by school principals. This study used a qualitative naturalistic approach with a descriptive type which took place at SMAIT Al Multazam 2 Linggajati, Kuningan using data collection techniques, observation, interviews, and documentation. The research results show that: 1). The Head of School Performance in general has shown good and optimal performance and meets the standards and indicators that have been set. This is explained in the "school work plan (RKS)" as the principal's plan for carrying out work programs and increasing teaching staff in schools. 2) There are several factors that influence the performance of school principals in improving the quality of teaching staff including the geographical conditions of the school, educators who teach not according to their educational background, and a conducive environment. 3) The Principal has made efforts to improve the quality of Educators through empowerment activities and school programs such as academic supervision, subject teacher deliberations (MGMP), self-evaluation (EDS), In House Training (IHT) and entrepreneurial activities intended for educators and students. Based on the research results, it can be interpreted that the principal has done his job optimally in improving the quality of teaching staff through supporting activities to improve the quality of teaching staff and based on national education standards.